ORGANIZATIONAL MANAGEMENT OF THE INDONESIAN NATIONAL SPORTS COMMITTEE (KONI) KEBUMEN REGENCY - Fauzi . Rizkian; Limpad . Nurrachmad (Nusa Cendana University, 2022)
The purpose of this study was to determine sport good governance, organizational management, and the impact of developing KONI's achievements in Kebumen Regency. The method used in this research is a qualitative method. Using good governance and organizational management interview instruments. And analyzed using the theory of Miles and Huberman. The results of the analysis show that the sport good governance indicator, namely the absence of transparency, is due to the fact that they do not yet have a website. Most of the indicators in the Democratic Process have been running well, which is indicated by the application of the democratic process for the open election of the chairman. Then Checks and Balances have been implemented, namely having a code of ethics and integrity for all its members. A good solidarity sports organization must have a great responsibility for the welfare of its members and community involvement. The conclusion that can be drawn is that overall the sports good governance of KONI Kebumen Regency has already been implemented, namely Democratic Process, Checks and Balances, solidarity, but there is one indicator that cannot be implemented, namely Transparency, so there needs to be a policy that emphasizes more on this policy. Meanwhile, the results of organizational management have generally referred to the theory of sports organization management. As well as the impact according to sport in the development of sports achievements so far, sports are inadequate in terms of facilities and infrastructure as well as a small budget.